Hubungan Academic Self Eficacy dengan Academic Resilience - Arifin Nur Budiono; Wiwik Suryani; Dian Triana (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
Research on the relationship between academic self-efficacy and academic resilience of class X students of SMK Kartini Jember for the 2020/2021 Academic Year with respondents studied as many as 92 students out of 120 students was taken with the research described. The techniques used are polling and meeting strategies. Side effects of information investigation using the second item equation to break the relationship between two factors, namely academic self-efficacy with academic resilience of class X students of SMK Kartini Jember for the 2020/2021 Academic Year. Based on the results of the study by utilizing the help of the SPSS application, it is known that a very large value is 0.00, so conclusions are drawn from the hypothesis, namely Ha: there is a relationship between academic self-efficacy and academic resilience of class X students of SMK Kartini Jember for the 2020/2021 Academic Year. Ho: there is no relationship between academic self-efficacy and academic resilience of students of SMK Kartini Jember for the 2020/2021 Academic Year. The results of the study using the SPSS application are known to be of a large value of 0.00, then the critical value of 0.00 is below 0.05, so it tends to be considered that Ha is recognized and Ho is rejected. So the answer was obtained that there is a relationship between academic self-efficacy and academic resilience of class X students of SMK Kartini Jember for the 2020/2021 Academic Year. This proves that both factors are at a moderate level. Keywords: academic self efficacy; academic resilience